2017
DOI: 10.1007/s00464-017-5475-3
|View full text |Cite
|
Sign up to set email alerts
|

ICG fluorescence imaging for quantitative evaluation of colonic perfusion in laparoscopic colorectal surgery

Abstract: ICG fluorescence imaging is useful for assessing anastomotic perfusion in colorectal surgery, which can result in more precise operative decisions tailored for an individual patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
149
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(163 citation statements)
references
References 42 publications
9
149
0
5
Order By: Relevance
“…One study compared the anastomotic leakage rate in perfusion detection both with and without the use of ICG fluorescence imaging, which resulted in reducing the rate from 20% to 0% . Twenty‐one clinical trials reported the use of ICG as a NIR fluorescence agent with different imaging systems in intraoperative evaluation of colorectal anastomoses . ICG was often injected after anastomotic site selection to evaluate the effect of ICG in selecting the correct anastomotic site.…”
Section: Tissue Perfusionmentioning
confidence: 99%
“…One study compared the anastomotic leakage rate in perfusion detection both with and without the use of ICG fluorescence imaging, which resulted in reducing the rate from 20% to 0% . Twenty‐one clinical trials reported the use of ICG as a NIR fluorescence agent with different imaging systems in intraoperative evaluation of colorectal anastomoses . ICG was often injected after anastomotic site selection to evaluate the effect of ICG in selecting the correct anastomotic site.…”
Section: Tissue Perfusionmentioning
confidence: 99%
“…There were also reports that performing radioisotope could assess colonic blood ow and reduce suture insu ciency. 7,8 ICG uorescence imaging showed good intestinal blood ow in all cases. It was con rmed that there were no complications due to impaired blood ow, such as an anastomotic leak, intestinal necrosis, or colostomy.…”
Section: Discussionmentioning
confidence: 80%
“…76 Other options include visible light spectroscopy (VLS) and near-IR spectroscopy (NIRS) using indocyanine green (ICG; (firefly, spy, etc.). 74,77 Unfortunately, while some suggest change in operative planning based on results from VLS and NIRS, 77,78 comparison studies are limited and no clear values predictive of anastomotic complication currently exist. We use palpation and visual inspection of blood supply before and after anastomosis.…”
Section: Preventing Complications: Leak Stricture and Recurrencementioning
confidence: 99%